What do students engage with the most? A comparative study between high and low achieving students within online learning environments. (3rd July 2022) - Alqurashi, Emtinan
ABSTRACT: The purpose of the study was to explore the difference in student engagement between high achieving and low achieving senior undergraduate students who took all their courses entirely online at United States (US) higher education institutions. It aims to evaluate student engagement variables and compare them with student achievement to help instructors and institutions detect areas for improvement in student engagement that might impact student learning and achievement. This study analysed data collected from undergraduate senior-level students who responded to the National Survey of Student Engagement (NSSE) in the academic year of 2015/2016. Seven variables of student engagement were analysed. Results of the study show that high achieving students were significantly higher than low achieving students in higher-order learning, reflective and integrative learning, learning strategies, quantitative reasoning, and effective teaching practices. However, low achieving students were significantly higher than high achieving students in student–faculty interaction. No significant differences were found in collaborative learning.